A mechanistic PK/PD model for two anti-IL13 antibodies explains the difference in total IL-13 accumulation observed in clinical studies. Issue 5 (3rd July 2016) - Tiwari, Abhinav; Kasaian, Marion; Heatherington, Anne C.; Jones, Hannah M.; Hua, Fei
ABSTRACT: IMA-638 and IMA-026 are humanized IgG1 monoclonal antibodies (mAbs) that target non-overlapping epitopes of IL-13. Separate first-in-human single ascending dose studies were conducted for each mAb. These studies had similar study designs, but mild to moderate asthmatics were recruited for the IMA-638 study and healthy subjects were recruited for the IMA-026 study. IMA-638 and IMA-026 showed similar pharmacokinetic (PK) profiles, but very different total IL-13 (free and drug bound IL-13) profiles; free IL13 was not measured. IMA-026 treatment induced a dose-dependent accumulation of total IL-13, while IMA-638 treatment led to a much smaller accumulation without any clear dose-response. To understand the differences between the two total IL-13 profiles and to predict the free IL-13 profiles for each mAb treatment, a mechanistic PK/pharmacodynamic model was developed. PK-related parameters were first fit to the mean PK profiles of each mAb separately; thereafter, the target-related parameters were fit to both total IL-13 profiles simultaneously. The IL-13 degradation rate was assumed to be the same for asthma patients and healthy subjects. The model suggests that an approximately 100× faster elimination of IL-13-IMA-638 complex than IL-13-IMA-026 complex could be responsible for the differences observed in total IL-13 profiles for the two mAbs. Furthermore, the model predicts that IMA-638 administration results in greater and more prolonged free IL-13 inhibition than equivalent dosing of IMA-026 despite similar binding KD and PK profile. In conclusion, joint modeling of two similar molecules provided mechanistic insight that the elimination rate of mAb-target complex can regulate the degree of free target inhibition.